Does laparoscopic appendectomy increase the risk of intra-abdominal abscess in children who have perforated appendicitis? - Akbıyık, Fatih; Ekberli, Günay; Çavuşoğlu, Yusuf Hakan (The European Research Journal, 2019)
Objective: The aim of this study is to compare the rates of intraabdominal abscesses (IAAs), in laparoscopic appendectomy (LA) and open appendectomy (OA) for perforated appendicitis in children.Methods: A retrospective database search of consecutive cases of children with a diagnosis of perforated appendicitis who underwent OA or LA by the first author or were operated under his supervision diagnosed with appendicitis between 2011 and 2014 and who underwent surgery as treatment was conducted.Results: Seventy-eight patients were included in our study. Forty-two and 36 patients underwent LA and OA, respectively. One case was converted from LA to OA. There was no statistically significant difference at superficial incisional surgical-site infections and IAA between groups but drain placement ratio and length of hospital stay was higher in OA group. Conclusions: The lack of difference in postoperative incidence of IAA supports the idea that LA does not increase the risk of IAA in perforated appendicitis. Although LA for perforated appendicitis in children has been intensely debated, our findings indicate that laparoscopic procedures performed by experienced pediatric surgeons will decrease the risk of complication and conversion to OA. Laparoscopy in children is a safe procedure for perforated, complicated appendicitis.